Impassioned belief - Ridge, Michael (Oxford Scholarship Online, 2014)
We all form judgments about what ways of life are worthwhile, what we are morally required to do and so on. These so-called "normative" judgments have seemed puzzling in part because they exhibit both belief-like and desire-like features. Traditional cognitivist theories hold that these judgments are beliefs rather than desires; traditional non-cognitivist theories hold that they are desires rather than beliefs. Each of these traditions tries to accommodate or explain away what the_x000D_other tradition handles so easily. One often gets the sense that the defenders of these increasingly complex theories are trying to force a square peg into a round hole. So-called "hybrid theories" try to have the best of both worlds by understanding normative judgments as constituted by both_x000D_belief-like and desire-like states
Keywords: Norm (Philosophy); Practical judgment.; Practical reason.; Norme (Philosophie); Jugement pratique.; Raison pratique.; PHILOSOPHY -- Ethics & Moral Philosophy.; PHILOSOPHY -- Social.; Practical judgment; Practical reason